“Lho, Kok Kesusu?” Tindak Tutur Fatis dalam Budaya Bertamu Masyarakat Candimulyo - Lestari, Azizah Wahyu (Crises on Languages and Literature, 2024)
Phatic expressions or abang-abang lambe in the visiting culture (mertamu) of the Javanese community in Candimulyo have an important role in forming social relationships closely related to culture. This research is motivated by the emergence of several interpretations of phatic forms, especially for people who do not fully understand phatic expressions in the visiting culture in Candimulyo. This research describes the phatic forms and functions of phatic expressions used in visiting activities in Grenggeng Village, Candimulyo, Magelang Regency. The data analyzed were in the form of phatic utterances of the Candimulyo community when visiting, which were obtained through direct observation and then described using qualitative descriptive methods. The results of the study showed that there were several phatic utterances in visiting activities, including (1) congratulations, (3) hopes, (3) invitations, (4) prohibitions, (5) humility, and (6) farewell. Several phatic particles such as lho, kok, ta, mbok, lah, dhing, and cen were also variations. Based on the research results, many functions of phatic expressions were found in the Candimulyo Community's visiting culture to confirm the conversation so that it continues. This shows that using various phatic expressions in the Candimulyo community's visiting culture is a unique character that functions as a form of respect for the conversation partner.